PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK ADVAN JENIS ANDROID DI SEMARANG (Students' Journal of Economic and Management, 2016)
This study aimed to analyze the effect of the variable quality of product, price and promotion of their perception pembeian decision Advan types android phone in Semarang.The data used in this research is the primary data, with the questionnaire as a research instrument, which is then processed with SPSS calculations. The population in this study is that people who buy mobile phones Semarang Advan types of android totaling 100 respondents. The sampling technique used purposive sampling means that sample deliberate manner in accordance with the requirements of sampelyang required. The analysis tool used is multiple linear regression. The results of this study showed that the significant positive effect between the perception of price to pembelian.terdapat decision is a no significant positive influence between product quality and the promotion of their purchasing decisions dominant variable influencing purchasing decisions is price perception. Keywords: Product Quality, Perceived Price, Promotion and Purchasing Decisions